A Vibration-based Electromagnetic Energy Harvester to Power Fault Monitoring Sensors used for Centrifugal Pumps - GILANI, SYED FAIZAN-UL-HAQ (2017)
Wireless vibration sensors are used for vibration data transmission of centrifugal pumps which is later analysed for early detection of faults. The periodic replacement of batteries in wireless sensors restrict the vibration monitoring of the centrifugal pump as it interrupts the wireless data transmission of the sensor. In that aspect, a vibration-based energy harvester can be used to tackle the issue of battery replacement among sensors. However, the conventional energy harvesters are unable to harvest the high-frequency vibrations of the centrifugal pump effectively. This is because the amplitude for a resonant energy harvester is drastically reduced at high vibration frequency. This reduction in amplitude negatively impacts the output voltage produced by the harvester. Therefore, this thesis presents a unique vibration-based energy harvester that effectively harvests the high-frequency vibrations of the centrifugal pump by utilising the vibration isolation technique to increase the relative velocity of the harvester and resulting in an increased output voltage. In that aspect, the centrifugal pump is thoroughly investigated as a suitable source for vibration energy harvesting. The design of the harvester is then presented based on the parameters obtained from the investigation. The proposed design of the VEH is modelled, fabricated and characterised on the vibration shaker accordingly. The developed prototype was able to generate a maximum open-loop voltage of 3.48 V and a closed-loop voltage of 1.63 V with an average power of 3.8 mW delivered to an optimum load of 700 Ω at a natural frequency of 200 Hz and an acceleration level of 1 g. The experimentation results are in good agreement with the simulation results as the average percentage error falls within an acceptable range of 6.15 %. A case study is also presented in this thesis whereby a ZigBee transceiver is successfully powered from the output generated by the VEH.